PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 7E TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII - Suci, Restie Amanda (Jurnal Edukasi dan Penelitian Matematika, 2023)
Understanding mathematical concepts is an important aspect to be achieved through learning mathematics. This study determine whether students' understanding of mathematical concepts in learning with the 7E learning cycle model is better than student learning through direct learning in class VIII of SMPN 4 Bukittinggi. This study used quasi-experimental design with The Nonequivalent Posttest Only Control Group Design. The population of this study were studentts of class VIII SMPN 4 Bukittinggi who were registered in the 2022/2023 academic year. Sampling wass done by random sampling technique. The research instrment was in the form of a final test which was evaluated using a hypothesis test, t test. Based on the analysis of statistical tests, it was concluded that H0 was rejected. This shows that the Learning Cycle 7E learning model influences students' understanding of mathematical concepts. Keywords– Learning Cycle 7E, Mathematical concepts understanding, Direct Learning